LOCAL ACTION AND GLOBAL AUDICENCES: ANARCHIST ACTIVITY IN CENTRAL AMERICA ACCORDING TO ITS ARCHIVES BETWEEN 1910 AND 1930 - Llaguno Thomas, José Julián (2016)
This paper presents an analysis of the anarchist presence in Central America in the early twentieth century from a conceptual and methodological reflection using as main sources anarchist publications published within and outside the region; and the most important historiographical literature to help contextualize the subject. It argues for an analytical perspective to develop the full potential of the study of militant networks, as well as an approach that combines time and space as interdependent and essential to broadly characterize the scope and limitations of anarchist action variables.